From climate risk to resilience: Unpacking the economic impacts of climate change in Malawi - Detelinova, Iva; Thomas, Timothy S.; Hammond, Wole; Arndt, Channing; Mukashov, Askar (International Food Policy Research Institute, 2023)
Climate change is not projected to materially alter Malawi’s climate profile. Instead, it is likely to exacerbate existing climate vulnerabilities by increasing the frequency and intensity of cyclones, floods, and droughts. This is largely due to increased uncertainty around future precipitation levels. These adverse effects have already started to materialize and are expected to increase substantially over the next decades, particularly if efforts to reduce global greenhouse gas emissions by high emitting countries are insufficient. Climate change is also projected to increase average annual temperatures across the country. Climate change is expected to significantly affect Malawi’s economy, mainly because of its dependence on climate-sensitive economic sectors and its low capacity to take adaptation measures due to preexisting macroeconomic vulnerabilities. Malawi’s sensitivity to climate shocks is underpinned by significant environmental degradation, in particular deforestation, watershed degradation, and poor soil management. The two main impact channels are likely to be agriculture and road infrastructure. In agriculture, the increased uncertainty around future precipitation levels in Malawi will likely result in higher variability in crop yields. Climate change is projected to exacerbate preexisting environmental degradation challenges, including soil erosion. These effects are particularly problematic due to Malawi’s high poverty rate, lack of economic diversification (the agriculture sector represents one-third of the economy and employs over 70 percent of the workforce), and significant dependence on rainfed production (about 80 percent of the population). Climate change is likely to significantly impact Malawi’s road infrastructure, mainly due to increased risk of flooding, which would have broader economic and social knock-on impacts.